2014
DOI: 10.3184/175815514x13902927945697
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Functions in hen Reproductive Organs

Abstract: The ovary and oviduct of the hen are susceptible to various pathogenic microorganisms, and infections in these organs may not only contaminate the eggs, but also disorder the egg formation. The immune function of the ovary and oviduct is essential to protect these tissues from infection as well as for the production of hygienic eggs. This paper reviews recent studies on the host defence system in the reproductive organs with reference to their innate immune functions, with emphasis on the important role of Tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 85 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Besides, an innate and adaptive immune were triggered during the SE challenge. We found that the TLR4 , NOD1 , AvβD7 , and IL‐1β mRNA were upregulated significantly in the ovary, which suggested the ovary, as immune niche, had a local immune environment to defend the birds against SE invasion (Yoshimura, Mageed, Nii, Ariyadi, & Isobe, ).…”
Section: Discussionmentioning
confidence: 96%
“…Besides, an innate and adaptive immune were triggered during the SE challenge. We found that the TLR4 , NOD1 , AvβD7 , and IL‐1β mRNA were upregulated significantly in the ovary, which suggested the ovary, as immune niche, had a local immune environment to defend the birds against SE invasion (Yoshimura, Mageed, Nii, Ariyadi, & Isobe, ).…”
Section: Discussionmentioning
confidence: 96%
“…The ability of reproductive tissues to synthesise AvBDs and their regulation in response to pathogens may play an essential role in innate immunity in the ovary and oviduct, establishing localised defenses within the host. Synthesised AvBDs notably fortify the defense mechanism of reproductive organs (Yoshimura et al 2014) and offer protection against infection (Yoshimura 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) have emerged as a major component of the vertebrate pattern recognition receptor (PRR) repertoire, and can recognize conserved pathogen-associated molecular patterns (PAMPs) of bacteria, fungi, viruses and parasites as well as some self-ligands, such as host DNA in immune complexes and the malarial pigment hemozoin, (hemoglobin digested by malarial parasites), but not commensal microbes [ 1 - 3 ]. Upon activation by an agonist, TLRs induce the expression of a wide range of immunoregulatory and effector molecules [ 4 - 6 ], which take part in the regulation of immune cell maturation and the clearance of pathogenic microorganisms [ 5 , 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%